Reseñas bibliográficas - Fernández Rivas, Aránzazu; Vacas, Roser L; Herreros, O (Revista de Psiquiatría Infanto-Juvenil, 2010)
QUEEN BEES & WANNABES. Helping your daughter survive cliques, gossip, boyfriends, and the new realities of girl world Rosalind Wiseman, Three Rivers Press. New York, 2ª edición. 2009 CONSULTA PSIQUIÁTRICA EN PEDIATRÍA. En niños y adolescentes con enfermedad orgánica Shaw, Richard J. y de Maso, David R. 1ª Edición. Editorial Médica Panamericana. Buenos Aires, 2009. (Traducción de Diana Klajn; Mariano Scolari; Mariel Migueres). 402 pp. TREATING CHILD AND ADOLESCENT DEPRESSION Rey, Joseph M. y Birmaher, Boris (eds.). 1ª ed. Lippincott Williams & Wilkins. Philadelphia, 2009. 360 pp. MEYLER’S SIDE EFFECTS OF PSYCHIATRIC DRUGS Aronson, Jeffrey K. (ed.). 1ª. Edición. Elsevier. Ámsterdam, 2009. 732 pp. PEDIATRIC AND ADOLESCENT PSYCHOPHARMACOLOGY. A Practical Manual for Pediatricians Greydanus, Donald E.; Calles, Joseph L. y Patel Dilip R.(eds.) 1ª ed. Cambridge University Press. Cambridge, 2008. 301 pp. OBESIDAD INFANTIL. Prevención, intervenciones y tratamiento en Atención Primaria Sandra G. Hassink. Editorial Médica Panamericana, 2010 (traducción del original del año 2006). 334 pp. A CLINICAL GUIDE TO PEDIATRIC WEIGHT MANAGEMENT AND OBESITY Sandra G. Hassink. Lippincott Williams & Wilkins. Philadelphia, 2007. 205 pp.